2018
DOI: 10.3389/fnhum.2018.00394
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Attenuates fNIRS Signal Associated With Painful Stimuli in the Medial Frontopolar Cortex (medial BA 10)

Abstract: Functional near infrared spectroscopy (fNIRS) is a non-invasive optical imaging method that provides continuous measure of cortical brain functions. One application has been its use in the evaluation of pain. Previous studies have delineated a deoxygenation process associated with pain in the medial anterior prefrontal region, more specifically, the medial Brodmann Area 10 (BA 10). Such response to painful stimuli has been consistently observed in awake, sedated and anesthetized patients. In this study, we adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 101 publications
4
43
1
Order By: Relevance
“…fNIRS was implemented as an alternate approach to probe CNS function, as MRI-based assessments are not easily feasible for many FOP patients. This study, in conjunction with other recent efforts, demonstrates fNIRS's utility towards elucidating central pain mechanisms [9,35]. However, limitations are noted.…”
Section: Discussionmentioning
confidence: 69%
“…fNIRS was implemented as an alternate approach to probe CNS function, as MRI-based assessments are not easily feasible for many FOP patients. This study, in conjunction with other recent efforts, demonstrates fNIRS's utility towards elucidating central pain mechanisms [9,35]. However, limitations are noted.…”
Section: Discussionmentioning
confidence: 69%
“…Another study with fibromyalgia found lower motor cortex (MC) activation during repetitive movement of the finger-tapping task at pressing a push-button panel with the right-hand thumb in two modalities—slow and fast 20 . Again, in an earlier study in healthy subjects, morphine attenuated the pain signal measured by fNIRS in the medial Brodmann’s area 10 and primary somatosensory cortex (S1) 21 . In comparison, fibromyalgia patients showed an increase in HbO at the dorsolateral prefrontal cortex (PFC) upon painful stimulation compared to healthy controls 19 .…”
Section: Introductionmentioning
confidence: 73%
“…Our thesis is that nociceptive pathways are intact and that similar patterns of activation would be present even in the context of analgesia. With respect to the latter, opioids do not completely block nociceptive signals produced by significant nociceptive activators 33 such as surgical incisions. Therefore, the use of a different group (awake) of individuals was to evaluate signal processing using a parallel format for determining "ongoing pain/ nociception.…”
Section: Subjectsmentioning
confidence: 99%